A new variety of spring barley Boyarin and elements of varietal technology - I. N. Shchennikova; T. K. Sheshegova; O. M. Snigireva (Аграрная наука Евро-Северо-Востока, 2023)
The development of the Boyarin spring barley variety was carried out in 2008-2022, the improvement of varietal agricultural technology – in 2021-2022 in the soil and climatic conditions of the Kirov region. The Boyarin spring barley variety is characterized by a high yield (up to 6.15 t/ha in 2017), in some years exceeding the Belgorod 100 standard (by 0.9 t/ha in 2018). The variety is medium-early, the duration of the growing season is from 76 to 97 days; forms a highly productive stem (390 pcs/m2) due to good survival and bushiness of plants (2.0 pcs/plant), has a strong straw and is characterized by high resistance to lodging (5.0 points). The weight of 1000 grains is up to 47 g, the nature is up to 683 g/l, the protein content in the grain is up to 12.2 %. According to the quality of grain, it belongs to the varieties of grain-forage use. Since 2023, the Boyarin variety has been included in the State Register of Breeding Achievements Approved for Use in the Volga-Vyatka region. The article provides a scheme for creating a new variety of spring barley Boyarin and its economic and biological characteristics. When developing elements of varietal technology, new biofertilizers (Azolene, Azotovite, Phosphatovite, Kalivite, Nitroslak) andbiofungicides (Pseudobacterin, Flavobacterin, Alirin) were tested, which were used to treat seeds and plants in the "tillering" and "earing" phases. In relatively arid vegetation conditions (HTC = 1.23), no statistically significant yield increases were obtained from the use of all the studied preparations. With excessive moisture during the growing season of plants (HTC = 2.20) relatively high yield increases (1.31-1.58 t/ha with LSD05 = 0.50) were obtained in variants using biofertilizers Phosphatovite (seed treatment), Azotovite (plant treatment in the "earing" phase) and Kaliivit (treatment of plants in the "tillering" phase). The best biological protection against root rot at the level of 60.5 % was provided by the treatment of seeds with Nitroslak biofertilizer, which is not only a nitrogen fixator and phosphate immobilizer, but it also contains a binary mixture of microorganisms antagonists of phytopathogens.